The Effect of Intermittent Fasting on Salivary Inflammatory Cytokines and Dopamine Levels - Fayyad, Elyazia; Anoud, Zumurd Al; Habra, Abdulkader; Meshal, Hussein Al; K.G, Aghila Rani; Saqan, Roba; Rizvi, Zuha; Awad, Manal; Al-Rawi, Natheer (European Journal of Dentistry, 2025)
The current study elucidates potential alterations in inflammatory cytokines and dopamine (DA) levels in saliva following a 21-day fasting regimen during Ramadan and explores their associations with mental health parameters.Forty-four healthy young university students (22 females and 22 males; median age 22 (2) and body mass index 23.40 (6.23) were enrolled, and saliva samples were collected before and after fasting. Cytokine and DA levels were quantified by ELISA and LEGENDplex Human Inflammation Panel, respectively. Participants also completed the Patient Health Questionnaire-9 and Depression Anxiety Stress Scales questionnaires to assess mental health.Data analysis was performed using SPSS. Differences between pre- and postfasting were tested using Wilcoxon's signed-rank test. Mann–Whitney's U test determined disparities in DA and cytokine levels across sex. Simple and multiple linear regression analyses were performed to identify the factors influencing the change in DA. Correlation analysis was employed to explore the relationships between the changes in DA and cytokine levels before and after fasting.A significant increase in inflammatory cytokines such as interleukin (IL)-1β, interferon-α2, tumor necrosis factor-α, IL-23, IL-33, and IL-8 was observed after fasting. Anti-inflammatory cytokine, IL-10, levels remained unchanged. Females had significantly higher levels of proinflammatory cytokines before fasting compared with males, but no significant gender differences were observed after fasting. The current study also showed a significant decrease in DA levels after fasting; however, no significant difference in DA levels across genders was noted. Self-reported mental health status did not significantly change before and after fasting. Multiple linear regression analyses did not suggest potential associations between these variables and changes in DA levels before and after fasting. However, correlation analysis indicated that the change in inflammatory cytokine levels was inversely related to changes in DA levels.Fasting during Ramadan significantly increased salivary cytokine levels and decreased DA levels, indicating potential relationships between immune factors and mental well-being. The findings highlight the complex interplay between inflammation, immunity, and DA regulation during fasting. Further research is warranted to elucidate the potential long-term effects of these associations and their implications for mental health and well-being.
Keywords: Ramadan fasting; dopamine; saliva; interleukins; ELISA